2013
DOI: 10.1002/eet.1614
|View full text |Cite
|
Sign up to set email alerts
|

The Green Economy: Incremental Change or Transformation?

Abstract: The concept of the green economy presented in three reports from leading global organizations is examined in this paper. These include the United Nations Environment Programme's Towards a Green Economy, the World Bank's Inclusive Green Growth and the Organisation for Economic Co‐operation and Development's Towards Green Growth. The main critiques of the concept of the green economy are also considered. Contrary to views that the green economy merely represents ‘green‐washing’ and tweaking of the current econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(71 citation statements)
references
References 16 publications
(19 reference statements)
0
56
0
Order By: Relevance
“…The green economy is a relatively new concept, and many aspects of it are controversial [6]. Many academics, even those familiar with the discourse relating to sustainability, are unconvinced about the merits of the green economy as a concept, or how it is being incorporated into policy [48][49][50]. This may account for its relatively slow uptake in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…The green economy is a relatively new concept, and many aspects of it are controversial [6]. Many academics, even those familiar with the discourse relating to sustainability, are unconvinced about the merits of the green economy as a concept, or how it is being incorporated into policy [48][49][50]. This may account for its relatively slow uptake in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…taking people's knowledge, experiences and aspirations into account) (Gough and McGregor 2007;Fritz et al 2009;Narayan et al 2009;Borel-Saladin and Turok 2013;Arthurson 2002;Mansuri and Rao 2004). These policy processes need to be contextually sensitive (Fritz et al 2009;Borel-Saladin and Turok 2013), and encourage participatory governance and capacity building to enhance such participation (Sachs 2004a, b;Lawson 2010).…”
Section: Social Inclusivenessmentioning
confidence: 99%
“…It has been shown that greening the economy can have considerable positive impacts to stimulate growth as well as improve the environment (Borel-Saladin & Turok, 2013a, 2013b. Tapping into this potential is of particular importance for a country such as South Africa with its high levels of unemployment as well as carbon emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding critiques about 'green-washing ' Borel-Saladin & Turok (2013a) contend from an examination of the international experience that the greening of the economy potentially can result in substantive and transformative changes towards the goal of sustainable development. In the case of South Africa the greening of the economy has become an important policy issue for two major reasons, namely the high level of national unemployment and the high carbon impact of the economy (Borel-Saladin & Turok, 2013b: 1).…”
Section: Introductionmentioning
confidence: 99%